Building Community Capacity in Southwest Virginia - Tauna Gulley (Rural Nurse Organization; Binghamton University, 2012)
Asset Based Community Development (ABCD), a guide for building healthier communities, was used to promote positive change in a rural southwest Virginia community. This paper illustrates how community assets were recognized and social capital increased as children painted a mural depicting the history of the community. A literature review of successful community building partnership models is provided and implications for nursing education are discussed, including suggestions for teaching collaboration skills for effective community partnering.